Neoadjuvant Radio(chemo)therapy for Breast Cancer: An Old Concept Revisited - Matuschek, Christiane (Breast Care (Basel), 2020)
BACKGROUND: The international standard of care for the treatment of high-risk breast cancer (BC) consists of neoadjuvant chemotherapy (NACT) and surgery followed by adjuvant whole breast/chest wall irradiation. In this setting, the time interval from the start of NACT to the end of radiotherapy (RT) is usually postponed to 6 months or longer. In addition to this, a high percentage of capsular fibrosis may occur when breast implants are irradiated. Most of these disadvantages could be avoided by using preoperative RT (PRT). PRT is already the standard of care in several other tumor entities (rectal cancer, esophagus carcinoma, lung cancer, and soft tissue sarcoma). Nevertheless, PRT in BC has been tested in several trials, but randomized prospective trials using modern radiation technology and systemic therapies are lacking. The available evidence summarized in this review indicates that PRT may improve survival and reduce long-term toxicity in patients with a higher risk of recurrence and should be consequently tested in a randomized trial. SUMMARY: Prospective, randomized trials concerning PRT in high-risk BC are needed. We plan to conduct a NeoRad trial (NACT followed by PRT in high-risk BC). KEY MESSAGES: Prospective, randomized studies concerning PRT in high-risk BC are needed.